2020
DOI: 10.1097/olq.0000000000001165
|View full text |Cite
|
Sign up to set email alerts
|

Ingenol Mebutate Gel 0.05% in the Treatment of Anogenital Warts: A Prospective Controlled Trial Comparing It With Topical Podophyllin Solution 25%

Abstract: Background Anogenital warts (AGWs) are a common therapeutic challenge. All therapies are associated with burning, pain, and frustrating high rate of recurrence. The search for a new alternative continues. Recently, a diterpene ester extracted from the Euphorbia peplus plant (ingenol mebutate [IM]) has been shown to possess activity against AGWs. Objective This study aimed to compare and evaluate the therapeutic efficacy and safety of topical 0.05% ingen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…27 Previous studies with podophyllin treated patients showed low clearance rates of 37%-63% and high rates of recurrence (42%-60%). 26,28,29 Our work supports the earlier findings and demonstrates that 9 of 28 (32.1%) patients treated with podophyllin had a complete response, and the recurrence rate was detected in seven patients (77.8%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…27 Previous studies with podophyllin treated patients showed low clearance rates of 37%-63% and high rates of recurrence (42%-60%). 26,28,29 Our work supports the earlier findings and demonstrates that 9 of 28 (32.1%) patients treated with podophyllin had a complete response, and the recurrence rate was detected in seven patients (77.8%).…”
Section: Discussionsupporting
confidence: 91%
“…24 Genital warts are commonly treated with podophyllin, a cytotoxic substance obtained from Podophyllum peltatum and Podophyllum hexandrum. 25 Human skin keratinocytes infected with the human papillomavirus are prevented from proliferating by podophyllin, 26 which inhibits mitotic activity in rapidly dividing cells by preventing the positioning of chromosomes on the spindle during metaphase of mitosis due to a mixture of antimitotic chemicals, of which podophyllotoxin is the primary component. 27 Previous studies with podophyllin treated patients showed low clearance rates of 37%-63% and high rates of recurrence (42%-60%).…”
Section: Discussionmentioning
confidence: 99%
“…1 Currently, for the treatment of anogenital warts (AGW), a wide variety of modalities are available, including imiquimod, podophyllin, podophyllotoxin, cryotherapy, carbon dioxide laser, and surgical removal. 2 Other medical treatments such as Ingenol mebutate 3,4 and nitrizinc 5 have been recently reported to be effective in several studies, but no approach has been shown to be universally successful, and failure of treatment and recurrence after the initial clearance are seen after performing any form of treatment. So, the treatment of AGW has always been a challenge for investigators.…”
Section: Introductionmentioning
confidence: 99%
“…AGW are benign epithelial tumors caused by an infection with certain types of human papillomavirus (HPV) [ 4 ]. Many individual case reports, smaller case series, and initial pilot studies have shown, that IM gel application effectively and quickly removes AGW [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In most cases, a single application of the gel was sufficient to ablate the warts within 24 h. After 8 h, the treated warts showed clinical signs of necrosis and peeled off within the next 24 h. Some patients felt severe pain at the treatment site, which peaked after 8 h and quickly ameliorated over the next half day.…”
Section: Introductionmentioning
confidence: 99%